2017
DOI: 10.1515/sab-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Honey Buyers’ Behaviour by Conjoint Analysis

Abstract: A marketing analysis of Czech consumers' behaviour when buying honey is discussed from the viewpoint of price, origin, honey type, crystallized sugar, and organic quality aspect. The surveyed target groups of honey consumers, who are examined also with respect to their education level, are from Prague and the Central Bohemian Region. The original premise of this research was the hypothesis that, when buying honey, customers focus primarily on its price and type. This hypothesis was verified by conjoint analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…In line with other research (Alibabić et al, 2017;Šánová et al, 2017), the present work reveals clustering is a useful methodology for defining different honey types, consumer segments and for bringing about some nuances in preferences.…”
Section: Discussionsupporting
confidence: 90%
“…In line with other research (Alibabić et al, 2017;Šánová et al, 2017), the present work reveals clustering is a useful methodology for defining different honey types, consumer segments and for bringing about some nuances in preferences.…”
Section: Discussionsupporting
confidence: 90%
“…In more depth, according to previous studies [20,23], consumers are interested primarily in the price and origin of honey, while the color affects consumers' subjective perception of honey quality during purchase. Similarly, Murphy and colleagues [48], by interviewing Irish consumers, showed that price, color and origin of products were quality attributes strongly affecting consumers' choice.…”
Section: Consumption Of Honey: Theoretical Frameworkmentioning
confidence: 99%
“…The increasing importance of honey among the agri-food products has evoked in the last years the interest of several researchers, who analyze the most important factors influencing consumers' behavior [20][21][22][23]. However, few studies have analyzed the effect of therapeutic properties on consumption behavior [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, respondents were asked to express if they consumed eucalyptus honey in the past and if they pay attention to honey price in the choice process [9]. Moreover, consumers were asked to express their interest toward some quality attributes of eucalyptus honey (such as color, taste, variety, viscosity, therapeutic properties, brand, organic certification, geographical indication, and Italian origin) [9,13,33].…”
Section: The Questionnairementioning
confidence: 99%
“…The increasing importance of honey among foods has pushed several researchers to study the factors influencing consumer behavior [9,[13][14][15][16]. In fact, honey is popular among consumers for its various nutritional aspects [17].…”
Section: Introductionmentioning
confidence: 99%